TEODISI ISLAM ESOTERIS: PEMIKIRAN ISA NUR AL-DIN AHMAD AL-SYAZILI TENTANG TUHAN DAN KEJAHATAN - Muhammad Nur Prabowo Setyabudi (Indonesian Journal of Islamic Literature and Muslim Society, 2018)
Theodicy was born as a response to the problem of evil and its relationship to the power of God, and at the same time, as an assertion of Omnipotence, Omnibenevolence, and Omniscience of God. This article presents the interpretation of Frithjof Schuon's thought or Shaykh Isa Nur al-Din Ahmad as a Muslim thinker of the tradition of Perennialism philosophy that emphasizes universalism and esoterism. The article describes Schuon's principal thought concerning theodicy, especially how esoteric Islamic theodicy sees the nature of evil, the relationship of evil with the free will of humans and determination of God (predestination). Furthermore, this article tries to draw the extent to which esoterism is supportive and coherent with texts that are exoterically expressed in the Qur'an. Basically, esoteric Islamic theodicy parallels with the principle of Islamic mysticism. In the last part, this article tries to take the moral significance of the notions of esoteric Islamic theodicy.